Analisis Firewall Demilitarized Zone dan Switch Port Security pada Jaringan Universitas Putra Indonesia YPTK - Syafri Arlis; Sahari (Universitas Putra Indonesia YPTK Padang, 2019)
The development of information technology so rapidly, greatly helped the works of man. On the one hand man to be very helpful, but on the other side of the system's security level to rise sharply so that in essence the sides of human life is in a threatened position. The techniques of network security systems and precautions against attacks on information systems continue to be developed so that the integrity, availability and confidentiality in an information system becomes more secure. One way is by building a network security system and attack prevention system. In this paper, the authors construct a computer network security systems using a firewall Demiliteralized Zone (DMZ) by using IPtables which is the standard of Linux systems and and Switch Port Security (SPS). Utilization by combining these two technologies to achieve maximum levels of security and is able to block the intruder will attempt an attack with a variety of attacks identified.